Lewis Acid‐Catalyzed C(sp3)–C(sp3) Bond Forming Cyclization Reactions for the Synthesis of Tetrahydroprotoberberine Derivatives. Issue 13 (4th May 2017) - Li, Jianjun; Qin, Cong; Yu, Yang; Fan, Huaqiang; Fu, Yiwei; Li, Hao; Wang, Wei
Abstract: An efficient Lewis acid‐catalyzed C( sp 3 )–C( sp 3 ) bond forming annulation reaction has been developed. This strategy serves as a new method for the facile synthesis of tetrahydro‐5 H ‐isoquinolino[2, 1‐ g ][1, 6]naphthyridine derivatives. A wide range of 2‐methylquinoline‐3‐carbaldehydes and 1, 2, 3, 4‐tetrahydroisoquinolines can be applied for this process to afford structurally diverse tetrahydroprotoberberine derivatives in excellent yields. Abstract :